SONSBEEK '16 : transACTION : Kids doe boek. - Smulders, Edith (Arnhem : Stichting Sonsbeek Internationaal, 2016)
ter Avest, Alphons ; Jatiwangi Art Factory ; Bell, Richard ; de Jong, Folkert ; Biscotti, Rossella ; de Boer, Maze ; Prawoto, Eko ; Gupta, Shilpa i.s.m. Harro, Buro ; Slavs and Tatars ; van Braak, Kevin ; Cordero, Louie ; KUNSTrePUBLIK ; Cinema Caravan ; Rothuizen, Jan ; Voerman, Rob ; Vanhoe, Reinaart ; Kotátková, Eva ; Soekarna, Marishka ; Sivanski ; Nnamari ; Naamloozz ; Magee, Fintan ; Museum Arnhem: transHISTORY
boek